Comparative Effects of Liquid and Solid Concentrated Growth Factors, and Injectable and Advanced Platelet-Rich Fibrin on Proliferation and Differentiation of Human Dental Pulp Stem Cells - Talebi Ardakani, Mohammadreza; Noorizadeh, Sarah; Talebi, Mohammad Hossein; Talebi, Amir; Azadi Hossein Abad, Alireza (Galen Medical Journal, 2024)
Background: This study compared the effects of liquid (L-CGF) and solid (S-CGF) concentrated growth factors, and injectable (I-PRF) and advanced (A-PRF) platelet-rich fibrin on the proliferation and differentiation of human dental pulp stem cells (DPSCs). Materials and Methods: Blood samples were collected to prepare A-PRF, I-PRF, L-CGF, and S-CGF according to the standard protocols. DPSCs were exposed to the biomaterials, and their proliferation was quantified after 24 hours and 5 days using the methyl thiazolyl tetrazolium (MTT) assay. Cell differentiation was histologically assessed by Alizarin red staining. Expression of osteocalcin (OCN), osteopontin (OPN), and RUNX2 genes was assessed in non-osteogenic medium, and osteogenic medium after 7 and 14 days by real-time polymerase chain reaction (PCR). Results: The mean cell proliferation was not significantly different among the study groups (P=0.324) and did not significantly change over time (P=0.346). S-CGF, L-CGF, and A-PRF showed a significant difference in OCN expression (P<0.001). The mean expression of OCN at 7 days was significantly lower in non-osteogenic medium. The mean expression of OCN and OPN at 7 days was significantly lower than 14 days. The mean expression of OPN at different time points was significantly different in A-PRF (P<0.002), L-CGF (P<0.003), and I-PRF (P<0.003) groups. The mean expression of RUNX2 was significantly different at different times in L-CGF group, and a significant difference existed in the expression of RUNX2 in non-osteogenic medium and at 14 days. Conclusion: Within the limitations of the present study, the results showed that A-PRF, I-PRF, L-CGF, and S-CGF can increase the proliferation and differentiation of human DPSCs by regulating gene expression, and can be suitable options for osteogenesis. There was no significant difference in terms of mean cell proliferation among the study groups.